Improvement in Quality of Sales Tax Assessments in West Bengal: A Study. (December 2016) - Kumar, Binod; Ghosh, Malay
The major source of own tax revenue of a State in India is Sales Tax. The Sales Tax administration in the State of West Bengal has undertaken a paradigm shift in last five years. Discretionary assessment of the tax-payers has been replaced by intelligent, objective and risk-based selection method. Replacement of unilateral discretionary demand by adjudication through introduction of draft order has established transparency and equity in the system. Distribution of hearing cases over the periods instead of completing them towards the end of the limitation has increased the quality of assessment. Electronic storage of records and electronic service of notices has increased efficiency of the tax administration. Use of data analytics in assessment and audit has resulted in growth in per cent of collection of assessed demand compared to previous years. JEL Classification: H21, H71, M48, K34